A new framework for the interpretation of IgE sensitization tests. Issue 11 (15th August 2016) - Roberts, G.; Ollert, M.; Aalberse, R.; Austin, M.; Custovic, A.; DunnGalvin, A.; Eigenmann, P. A.; Fassio, F.; Grattan, C.; Hellings, P.; Hourihane, J.; Knol, E.; et al.
Abstract: IgE sensitization tests, such as skin prick testing and serum‐specific IgE, have been used to diagnose IgE‐mediated clinical allergy for many years. Their prime drawback is that they detect sensitization which is only loosely related to clinical allergy. Many patients therefore require provocation tests to make a definitive diagnosis; these are often expensive and potentially associated with severe reactions. The likelihood of clinical allergy can be semi‐quantified from an IgE sensitization test results. This relationship varies though according to the patients' age, ethnicity, nature of the putative allergic reaction and coexisting clinical diseases such as eczema. The likelihood of clinical allergy can be more precisely estimated from an IgE sensitization test result, by taking into account the patient's presenting features (pretest probability). The presence of each of these patient‐specific factors may mean that a patient is more or less likely to have clinical allergy with a given test result (post‐test probability). We present two approaches to include pretest probabilities in the interpretation of results. These approaches are currently limited by a lack of data to allow us to derive pretest probabilities for diverse setting, regions and allergens. Also, cofactors, such as exercise, may be necessary for exposure to an allergen to result in an allergic reaction in specific IgE‐positive patients. The diagnosis of IgE‐mediated allergy is now being aided by the introduction of allergen component testing which may identify clinically relevant sensitization. Other approaches are in development with basophil activation testing being closest to clinical application.